Suction Pump Thoracic - Wahyu Ramadhan Putra; Sumber Sumber; Lamidi Lamidi (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2020)
Thoracic Suction Pump is a medical device used in the medical world to carry out the action of sucking fluid in the thorax cavity, then the liquid that has been sucked will be accommodated in a vacuum tube. Thoracic Suction Pump this model uses a DC voltage motor that is controlled by a motor driver by giving Pulse width modulation that comes from a minimum system circuit. In the use of this tool, the compiler uses 4 pressure selection modes, namely -5, -10, -15, and -20 kPa which is done by pressing the Push button Up and Down for selection of pressure. After the pressure is selected, the pressure value will appear on the 2 x 16 LCD display. This study used a pre-experimental type with One group post test design research design. After measurements and calculations are obtained the results of the pressure values ​​are read by the MPXV4115V sensor which is obtained the biggest error at maximum pressure with the setting of -10 obtained an average value of 2.78% error, in the -5 setting obtained an error value of 2.70%, in the settings -20 obtained an error value of 1.59%, and the smallest error in the setting of -15 obtained an error value of 1.09%.For the minimum pressure error the biggest error value with the setting of -10 is 0.33% error, the setting of -15 is 0.20%, the error-setting is 0.19%, and the smallest error is set - 20 obtained an error value of 0.18%.